Halal Compliance CV. Legacy and PT. Satria Catering Panorama: Contribution of Sharia Economics in Providing Food in Hospitals - Widodo, Pratomo Wahyu (PT FORMOSA CENDEKIA GLOBAL, 2025)
Halal certification plays an important role in the food industry, especially in the health sector, by ensuring that products meet Islamic sharia, hygiene and food safety standards. CV. Legacy and PT. Panorama Boga Satria, as a provider of halal food for RSUD Prof. Dr. Margono Soekarjo, strategically contributes to providing food that complies with halal principles, and supports the comfort of Muslim patients while maintaining the hospital's reputation. Competition between the two creates a positive dynamic that encourages innovation, improves service quality, and providing relevant solutions that meet hospital needs in various situations, including emergencies. Apart from providing direct benefits to patients and hospitals, their contribution to the halal food industry also supports the development of the sharia economy, expands accessibility, and opens up export opportunities, making Indonesia one of the world's halal industrial centers. The method used in this research is qualitative, with a case study approach. The results in this research are: CV: legacy and PT. Panorama Boga Satria plays a strategic role in providing halal food for patients at RSUD Prof. Dr. Margono Soekarjo, ensures that the products they produce support patients' medical needs while respecting religious and cultural values.